Less Is More? Field Evaluation of Short-Stature Banana Cultivars in a Mediterranean Environment - Idan Elingold; Avishi Londener; Amit Rimmer; Avi Tsarfaty; Gilad Hadar; Navot ‘Galpaz (Horticulturae, 2022)
The shift to cultivation of banana (‘Musa (AAA) Cavendish subgroup’) in screenhouses in Israel has resulted in a significant increase in plant height and, consequently, increased maintenance costs. Here, we evaluated the genetic approach to reducing plantation height. Advanced selections of the local cultivars ‘Adi’, ‘Zelig’, and ‘Gal’, selected for reduced height, were evaluated in the field. Growth and yield parameters were recorded and compared with the industry standard cv. ‘Grand Naine’ for four crop cycles. ‘Adi’ and ‘Zelig’ were shorter than ‘Grand Naine’, by 20% and 10%, respectively, whereas ‘Gal’ lost its short stature over the years. In addition, leaf area was reduced in the low-stature cultivars. Cumulative yield of ‘Adi’ and ‘Zelig’ was higher than that of ‘Grand Naine’, by 8.8% for ‘Adi’ and 5.0% for ‘Zelig’, due to higher plant density and number of harvested bunches. This multiyear study highlights ‘Adi’ and ‘Zelig’ as short-stature, highly productive cultivars with the potential for improved water-use efficiency.